Core-shell MXene/nitrogen-doped C heterostructure for wide-band electromagnetic wave absorption at thin thickness. Issue 20 (15th October 2022) - Xu, Xiaodan; Wang, Yanxiang; Yue, Yang; Wang, Chengjuan; Xu, Zhenhao; Liu, Dongming
Abstract: MXenes have been utilized to fabricate electromagnetic wave (EMW) absorbers owning to large aspect ratio, high electronic conductivity, and favorable hydrophilicity. In this work, the core-shell MXene/nitrogen-doped (N-doped) C heterostructure was firstly prepared via HCl and LiF etching, in-situ polymerization, and carbonization. When mixed with paraffin at a low filler loading of 30 wt%, the MXene/N-doped C hybrid reached a wide effective absorption bandwidth of 5.0 GHz (13.0 GHz–18.0 GHz) at a thin thickness of 1.72 mm. The stronger ability of attenuating EMWs promoted the absorption performance of MXene/N-doped C, overcoming the deficiency in the characteristics of impedance compared with its counterparts. This work provides a new insight in manufacturing MXene-based absorbers to alleviate EMW pollution by delicate structural design and effective multi-component strategy.